Functions of conserved centriole proteins in African trypanosomes - Scheumann, N (2012)
Centriole and basal bodies are related nine-fold symmetric microtubule-based eukaryotic organelles central to the organisation of cilia/flagella and centrosomes. Mechanisms of eukaryotic centriole and basal body assembly are mainly based on studies in animal systems. To understand which centriolar proteins are the universally important ones in the assembly across eukaryotes, a bioinformatic survey presented here investigates the distribution of centriolar and cilia-associated proteins across a diverse range of eukaryotes. This analysis showed also that the basal body function is ancestral to eukaryotes, whereas centrosomal components are specific to Holozoa (which include animals). It also suggested that the ancestor of all eukaryotes possessed a cilium/cilia not only with motility function but also with a sensory role. The most frequently conserved proteins in extant ciliated eukaryotes found in this analysis included SAS-6, SAS-4 and WDR16. To test whether these proteins are also important for basal body assembly in distantly-related species to metazoan and other model organisms where the proteins have been studied to date, the proteins were investigated in Trypanosoma brucei. I used a combination of genetic tools and microscopy techniques to demonstrate that SAS-6 but not SAS-4 is essential for basal body assembly in T. brucei. I showed that WDR16 is a stably integrated component of the transition zone and axoneme but not the basal body. Furthermore, I identified a novel SAS-6 like protein which localises to a position consistent with the basal plate and has the capacity to form into filaments. This thesis provides new insights into the evolution of centrioles and basal bodies, and into the function of conserved centriole proteins in T. brucei, a distantly-related organism to animals.